2011
DOI: 10.1111/j.1745-7599.2011.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving oral health in low-income pregnant women with a nurse practitioner-directed oral care program

Abstract: Because adverse pregnancy outcomes have been linked to periodontitis in numerous research studies, pregnant women must be educated about the importance of oral health and the necessity of a check-up. APNs are in an ideal position to educate women and assist them to obtain necessary oral health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 20 publications
6
50
0
Order By: Relevance
“…Seven home visiting programs [20, 23, 26&27, 36, 37, 38, 39] were reviewed as well whereas one intervention included both home visits and consultations at well-baby clinic. [22] Two studies [21, 38] reported including both urban and rural settings in their recruitment, five [23, 30, 34, 35, 37] were restricted to rural sites and three [25, 26, 28] to urbanized or metropolitan areas. Table 1 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven home visiting programs [20, 23, 26&27, 36, 37, 38, 39] were reviewed as well whereas one intervention included both home visits and consultations at well-baby clinic. [22] Two studies [21, 38] reported including both urban and rural settings in their recruitment, five [23, 30, 34, 35, 37] were restricted to rural sites and three [25, 26, 28] to urbanized or metropolitan areas. Table 1 …”
Section: Resultsmentioning
confidence: 99%
“…[24,25,26&27,28,32&33,36,40] Only one program [25] targeted pregnant women while all the other interventions focused on children’s oral health from birth till the age of five. In total 4846 caregivers participated in ten RCTs, 2569 of which were in the intervention arm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations